2015
DOI: 10.4317/medoral.20194
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of intraoral onlay block bone grafts on alveolar ridge augmentations: A systematic review

Abstract: Aim: The purpose of this study was to systematically review clinical studies examining the survival and success rates of implants placed with intraoral onlay autogenous bone grafts to answer the following question: do ridge augmentations procedures with intraoral onlay block bone grafts in conjunction with or prior to implant placement influence implant outcome when compared with a control group (guided bone regeneration, alveolar distraction, native bone or short dental implants.)? Material and Method: An el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 25 publications
7
82
1
3
Order By: Relevance
“…Such surgical techniques, however, are rather complex, have a high risk of complications, and result in increased time and cost of treatment [5, 6, 10, 13, 15]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such surgical techniques, however, are rather complex, have a high risk of complications, and result in increased time and cost of treatment [5, 6, 10, 13, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Several surgical techniques have been proposed for bone regeneration to allow for the subsequent placement of endosseous implants; these include onlay/inlay bone grating [6, 7], guided bone regeneration (GBR) with resorbable or nonresorbable membranes [8], alveolar ridge split [9], distraction osteogenesis [10], and maxillary sinus augmentation [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that under daily practice all these augmentation procedures may provide clinically acceptable results. Recent reviews have also reported a high implant survival of more than 90% for sinus augmentation [5, 15, 17, 21–23], lateral ridge augmentation [15, 19, 24, 25], for bone splitting [21, 26] as well as for three-dimensional augmentations using titanium mesh [27]. When augmentation procedures were compared to each other, the authors were not able to draw a clear conclusion on the superiority of a certain augmentation procedure or grafting protocol [15, 17, 21, 28].…”
Section: Discussionmentioning
confidence: 99%
“…When patient had worn denture for long time in the maxilla, we can expect severe alveolar bone resorption. Predictive treatment in severely resorbed anterior maxilla is block bone graft and delayed or immediate implant installation (4).…”
Section: Introductionmentioning
confidence: 99%